Open-Source IoT-Integrated SCADA System for Biomass Power Plant Monitoring - Palakorn Yuratsmeechan; Chalermchat Manop (My University, 2024)
This paper presents the development of a condition monitoring system for biomass power plant monitoring, employing the cloud open-source concept combined with notification and security features based on a SCADA system integrated with the IoT. Consequently, the open-source SCADA system is utilized to augment the control system's capabilities. This system will enable interactions among sensors, PLC, SCADA, HMI, and facilitate data storage in a cloud-based database. This integration ensures systematic and organized data collection, fostering efficient data analysis for operational processing within the biomass power plant system. Moreover, it permits rapid problem resolution through notifications via the remote Internet network system.
Keywords: Smart Agriculture and AI